Pengaruh Yoga Prenatal Terhadap Outcome Persalinan - Evrianasari, Nita; Yantina, Yuli (Politeknik Kesehatan Tanjung Karang, 2020)
Psychological problems experienced by women in childbirth difficulties are anxiety (52%) and doubt about their ability to cope with pain (43%). A study found 66,6% of prenatal yoga can improve the physical and psychological readiness of maternity mothers. Prenatal Yoga is a type of body, mind, and mental exercise that is one of the goals of training hip and surrounding muscles, to become stronger and elastic. The purpose of this study is to determine the influence of Prenatal Yoga on the outcome of childbirth which includes: Labor pain at a time of 1, long as 2, and Rupture Perinium on labor in BPM Yuli Artika SST Pesawaran. The type in this study is quantitative with the design of the experimental Quasi (pseudo experiment) research with the draft posttest only non-equivalent Control Group Design. The sample is a pregnant trimester III who meets the criteria of 60 respondents. Results showed that there is a prenatal yoga influence on pain during childbirth at the BPS Yuli Artika SST The participants were shown with the p-value 0,000 (<0,05), there is a prenatal yoga influence to a long time II childbirth at BPS Yuli Artika SST Pesawaran with p-value 0,000 (<0,05) and there is a prenatal yoga influence against the perineum tendon rupture at the BPS Yuli Artika SST Pesawaran with p-value 0,000 (<0,05). Given the many benefits of yoga for maternity mothers then prenatal yoga can be used as one of routine obstetrics that is given to pregnant during antenatal care, especially for BPS Yuli Artika Pesawaran.